2017
DOI: 10.1093/ofid/ofx259
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Outbreak in Kedougou, Southeastern Senegal in 2009–2010

Abstract: BackgroundIn Senegal, Chikungunya virus (CHIKV), which is an emerging mosquito-borne alphavirus, circulates in a sylvatic and urban/domestic cycle and has caused sporadic human cases and epidemics since 1960s. However, the real impact of the CHIKV sylvatic cycle in humans and mechanisms underlying its emergence still remains unknown.MethodologyOne thousand four hundred nine suspect cases of CHIKV infection, recruited from 5 health facilities located in Kedougou region, south-eastern Senegal, between May 2009 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The outbreak finding revealed that Chikungunya infection occurred equally between the genders and age groups. This study is consistent with a study conducted in Kedougou, Southeastern Senegal [8]. All cases of Chikungunya infection had fever, headache and joint pain (100%).…”
Section: Discussionsupporting
confidence: 91%
“…The outbreak finding revealed that Chikungunya infection occurred equally between the genders and age groups. This study is consistent with a study conducted in Kedougou, Southeastern Senegal [8]. All cases of Chikungunya infection had fever, headache and joint pain (100%).…”
Section: Discussionsupporting
confidence: 91%
“…In the CHIK seroprevalence studies of adults in Guadeloupe and Martinique in 2014, statistically significant differences were observed between the participants in terms of age and male sex 42 . In contrast, a study conducted in Senegal in 2009 and 2010 has found no difference in terms of sex and age between the confirmed cases of chikungunya 43 . Male sex was significantly associated with the risk of death among individuals in the state of Ceará (OR: 2.05).…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, the 2005 CHIKV outbreak in Karnataka, India, the 2006–2007 outbreak in Gabon, the 2008–2009 CHIKV outbreak in Thailand, and the 2010 outbreaks in Senegal and India reported dengue-like illness or undifferentiated fever with rash (Table 1) [34,41,44,45]. Furthermore, CHIKV infection of fetuses, neonates, or children caused no significant effects or long-term sequalae [44].…”
Section: Chikv In Neonates and Children After Re-emergencementioning
confidence: 99%
“…This genotype circulates in the western sub-Saharan regions of Africa and hasn’t been identified outside of this region. It has been documented in periodic outbreaks in Senegal and Nigeria and is typically associated with dengue-like illness accompanied by arthralgia [26,27,45,90,115,116,117,118]. In children, the disease is a minor and self-limiting febrile illness with no debilitating or neurological sequelae reported, even in recent outbreaks (Table 1) [45].…”
Section: Chikv In Neonates and Children After Global Expansionmentioning
confidence: 99%